Breeding and genetic improvement of spelt wheat (Triticum spelta) by interspecific hybridization - Diordiieva, I. P.; Riabovol, I. S.; Riabovol, L. O.; Babii, M. M.; Fedorenko, S. V.; Serzhuk, O. P.; Maslovata, S. A.; Liubchenko, A. I.; Novak, Z. M.; Liubchenko, I. O. (Regulatory Mechanisms in Biosystems, 2024)
Spelt wheat (Triticum spelta L.) is a high-value grain crop which is characterized by high protein, gluten and aminoacids content, high adaptive potential, resistance to diseases and high antioxidant activity. However, it is significantly inferior to soft wheat in terms of yield capacity. From crosses of spelt and soft wheat new promising genotypes can be obtained with improved quantitative traits due to introgression in the genome of spelt wheat of genetic material of soft wheat. In the research presented here based on hybridization of Triticum spelta L. × Triticum aestivum L. we obtained new forms of spelt which differ among themselves in terms of morphological characteristics, productivity and grain quality. As a result of the conducted research, a wide form-forming process in terms of plant height, ear morphology and grain threshing quality was recorded. The height of plants in F1 hybrids is inherited by the type of dominance of high stemness or intermediate inheritance was established. In the F2–F4 generations, the share of obtaining short-stemmed forms of spelt wheat was higher than with the use of short-stemmed varieties of common wheat as the maternal form. In F2 offspring, the inheritance of threshing quality by the type of dominant epistasis according to the 12 : 3 : 1 scheme was established. In F3–4 offspring, splitting according to ear morphology occurred with the appearance of not only typical forms of spelt wheat or common wheat, but also intermediate forms with different ratios of spike length and density. High-yielding (5.75–5.79 t/ha) short-stemmed (h = 78–89 cm) spelt wheat samples 1817 and 1559 with high grain quality indicators (weight of 1000 grains 64.4 g, protein content – 21.0%, gluten – 43.7%) were identified. Sample 13, which successfully combined high grain quality indicators in particular high protein content (26.2%), gluten content (55.8%), grain hardness (66.5 units), flour strength (340 alveograph units) was selected.